Política de ampliação do ensino fundamental para nove anos: percepções de professoras de uma escola da rede municipal de São Carlos - SP - Silva, Jaqueline Cristina da (Universidade Federal de São Carlos, 2020)
This research is inserted in the discussion field of enlargement of the primary education to nine years of duration, officialized, in Brazil, by the Law Nr. 11.274, in 2006. This law changed the length of primary education from eight to nine years, and defined the obligatory enrollment starting from 6 years old. The main objective of this study consists of analysing the perceptions from acting teachers in the three initial years of primary education about the implementation of such politics in the city of São Carlos/SP, having as reference the definitions of official documents from the Enlargement Program of the Primary Education to Nine Years, and the results of the most relevant researches in the subject. As methodological procedures, we used the documental research, the bibliographical research and semi-structured interviews with three acting teachers in the initial years of one public school in São Carlos/SP. We noted that, against so many publications, imprecisions, and amid so many mandatories from MEC, not everything that could be a potential factor for improvement in primary education actually occurred. Even though the official documents guided the realization of a reflection and a reorganization of the curriculum from primary education, the participant teachers of this research claimed that have not occurred collective discussions, not even a curriculum change, but, yes, a simple adaptation from previous years materials. Besides that, yet the documents indicated the necessity of restructuring of the space and the environment of the school, taking into account the singular characteristics of the smaller children, those aspects were not considered according to the interviewees. The playing, in its turn, highlighted by MEC as a fundamental specificity of the child, neither was incorporated as part of the routine of the children from primary years, as revealed. These situations were also recognized in the researches found in the databases, indicating that exist many aspects needing discussion and revision in the politics and in the practice of nine years primary education in Brazil. Thus, we can infer that the lacking of clarity and support by MEC, beyond the documents, as the amount of activities that popped up in the form of laws, programs or national assessments during the implementation of the Program, collaborated to education professionals attitudes based on individualized immediacy and spontaneity. This means that the nine years primary education in Brazil can be functioning like the studied school in this work, i.e., without an effective reflexion, discussion and legal and theoretical reasoning about the subject, reproducing, in practice, only the daily and previous experiences of the professionals from the former eight years primary education. Because of that, each school can be achieving different conclusions and conceptions, executing the politics from a particular and quick interpretation.
Educational politics of enlargement of the primary education to nine years of duration: perceptions of teachers from a school in the city of São Carlos - SP
Keywords: Anos iniciais do ensino fundamental; Ensino fundamental de nove anos; Política educacional; Inicial years of primary education; Nine years primary educacion; Educational politics; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL